Assessing Public Sector Environmental Accountability Through Performance Audit: The Case of Maldives - Rabeea Ibrahim; Aminath Shuaau Mohamed (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2022)
Environmental accountability has gained much-needed attention due to the growing concern about climate change and its impact. Given that environmental management has been a function of government, especially in developing countries like the Maldives, the country’s economy is dependent on its environment and natural resources, and the numerous efforts by the government toward environmental protection, promoting environmental accountability becomes crucial. At the heart of promoting environmental accountability lies the important role of public sector environmental performance audits. Through a qualitative research method of content analyses and unstructured interviews, this study aims to discuss the importance of environmental performance auditing in creating public sector accountability by alluding to the importance of environmental accountability and SAI Maldives’ role in creating public sector environmental accountability.